Characterization of alginate extracted from Sargassum latifolium and its use in Chlorella vulgaris growth promotion and riboflavin drug delivery - Shimaa R. Dalal (Nature Portfolio, 2021)
Abstract Alginates derived from macroalgae have been widely used in a variety of applications due to their stability, biodegradability and biocompatibility. Alginate was extracted from Egyptian Sargassum latifolium thallus yielding 17.5% w/w. The chemical composition of S. latifolium is rich in total sugars (41.08%) and uronic acids (47.4%); while, proteins, lipids and sulfates contents are 4.61, 1.13 and 0.09%, respectively. NMR, FTIR and TGA analyses were also performed. Crystallinity index (0.334) indicates alginate semicrystalline nature. Sodium alginate hydrolysate was evaluated as Chlorella vulgaris growth promoter. The highest stimulation (0.7 g/L biomass) was achieved by using 0.3 g/L alginate hydrolysate supplementation. The highest total soluble proteins and total carbohydrates were 179.22 mg/g dry wt and 620.33 mg/g dry wt, respectively. The highest total phenolics content (27.697 mg/g dry wt.), guaiacol peroxidase activity (2.899 µmol min−1 g−1) were recorded also to 0.3 g/L alginate hydrolysate supplementation. Riboflavin-entrapped barium alginate-Arabic gum polymeric matrix (beads) was formulated to achieve 89.15% optimum drug entrapment efficiency (EE%). All formulations exhibited prolonged riboflavin release over 120 min in simulated gastric fluid, followed Higuchi model (R2 = 0.962–0.887) and Korsmeyer–Peppas model with Fickian release (n ranges from 0.204 to 0.3885).